2018
DOI: 10.5194/isprs-archives-xlii-2-267-2018
|View full text |Cite
|
Sign up to set email alerts
|

Improving Image Matching by Reducing Surface Reflections Using Polarising Filter Techniques

Abstract: ABSTRACT:In dense stereo matching applications surface reflections may lead to incorrect measurements and blunders in the resulting point cloud.To overcome the problem of disturbing reflexions polarising filters can be mounted on the camera lens and light source. Reflections in the images can be suppressed by crossing the polarising direction of the filters leading to homogeneous illuminated images and better matching results.However, the filter may influence the camera's orientation parameters as well as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
(12 reference statements)
1
8
0
Order By: Relevance
“…The matte spots gave a smaller distortion of the sphere and the regions with a glossy surface were covered with a bigger distortion or lack of measurement. It is an interpretation supported by research from other authors showing problems with reflections [ 24 , 27 ]. For Agisoft Photoscan, larger differences from the scanner occurred only in a narrow strip in the lower, central part of the back of the dome.…”
Section: Comparative Photogrammetric Uav Measurement Of the Outer supporting
confidence: 72%
See 1 more Smart Citation
“…The matte spots gave a smaller distortion of the sphere and the regions with a glossy surface were covered with a bigger distortion or lack of measurement. It is an interpretation supported by research from other authors showing problems with reflections [ 24 , 27 ]. For Agisoft Photoscan, larger differences from the scanner occurred only in a narrow strip in the lower, central part of the back of the dome.…”
Section: Comparative Photogrammetric Uav Measurement Of the Outer supporting
confidence: 72%
“…One of the factors influencing the accuracy of photogrammetric measurements, especially in the case of objects with smooth or wet surfaces, was reflections. In the publication [ 24 ], the authors investigated the use of a polarization filter to reduce reflections on photographed objects in medical applications. The study concluded that a polarization filter can be used on a standard camera in structure from motion (bundle adjustment).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the system has been disassembled and the main pieces, the structure, scenes and four caryatids (Fig. 4), have been acquired and restored for educational and research purposes and in collaboration with local authorities, according to the acquisition process based on the comparison between textured models and orthophotos, both processed by photographic acquisition with different cameras and lighting photographic sets (listed below according to different decreasing costs): Cross-polarization images improve photogrammetric reconstruction and measurement on reflective surfaces (Wells et al, 2005, Conen et al, 2018. However, no errors occurred during photo alignment, regardless of the photographic set.…”
Section: Methodological Workflow and Toolkitmentioning
confidence: 99%
“…Next to the tripod, there were two external flashlights (Godox QS600II) synchronized with the camera. As known, (Conen et al, 2018, Menna et al, 2016 the photogrammetric matching of reflective surfaces may result in incorrect measurements, blunders, and noise in the final point cloud. To solve the problem of cross-polarisation can be used: polarizing filters can be mounted both on the camera lens and on the light source.…”
Section: Photogrammetric Surveymentioning
confidence: 99%